Faktor-Faktor yang Mempengaruhi TurnovernKaryawan pada Hotel Grand Mansion Blitar - Gunawan, Alexander Nicolla Sutrisno; Sahertian, Hallie Josias (Universitas Brawijaya, Indonesia, 2016)
Human resources is driving an important role in the organization or company. That for management activities goes well, the company should have employees who are experienced, high skilled, and efforts to managed the company as optimal as possible so that the company's performance increases. The common company's problems is employee turnover, so the purpose of this study was to analyze the factors that cause employee turnover at the Grand Mansion Blitar.Â The Grand Mansion Hotel chosed by authorsbecause the high rates of turnover that occurred in the hotel and theauthorswant to find and analyzed the factors that make the high rate of turnover. This study is exploratory research and aimed to identify the factors that caused employee turnover at the Grand Mansion Hotel. The data were collected by questionnaires that distributed to respondents who have stopped working from the Grand Mansion Hotel. The results showed thatthe caused of employeeÂ turnover is classified into four factors, that is the guarantee and the working environment, relationships within the company, personal needs, and the company's internal problems.